Psychometric Properties and Factor Structure of the Revised Epidermolysis Bullosa Burden of Disease (EB-BoD-R) Family Score - Gudrun Salamon; Sophie Strobl; Hélène Dufresne; Christine Bodemer; Anja Diem (Social Indicators Research, 2026)
Epidermolysis bullosa (EB) is a rare genetic disease defined by high fragility of the skin. The impact of this chronic disease extends beyond the physical and affects the psychosocial well-being and quality of life of not only the affected individuals but also their families. The Epidermolysis Bullosa Burden of Disease (EB-BoD) questionnaire aims to assess the impact of the disease on the family of those affected. Whereas the questionnaire has been partially validated in French, there is no validated English translation. Additionally, the original version is limited to assessing the quality of life of parents only. The objective of this study was to revise the EB-BoD to ensure its applicability to all relatives of individuals with EB, and to translate, culturally adapt and validate it in English. The EB-BoD revised was developed in three stages: (1) translation and cross-cultural adaptation, (2) content revision and thematic adjustment and (3) sample-based testing with 64 relatives of patients with all EB types to establish the psychometric properties of the English EB-BoD-R. The revised EB-BoD exhibits excellent reliability and internal consistency, with a Cronbach's α of 0.93. Exploratory factor analysis resulted in two distinct factors, Circumstances and Emotions . Convergent validity was demonstrated by strong correlations with the iscorEB-p and the SWLS (both p 0.167em<0.167em.001). Divergent validity was found in relation to social support F-SozU (ρ=-0.17, p 0.167em=0.167em.228). In conclusion, the English EB-BoD-R is an effective and reliable instrument for assessing the quality of life of relatives of EB patients.
Keywords: 300; Epidermolysis bullosa; Relative-reported outcome measures; Quality of life; EB-BoD; Family burden; Burden of disease; Test validity; Psychometric properties